Metode pembebanan biaya dan penentuan harga jual: studi kasus pada CV Emilysia Indo Bahari - Sengkandai, Elsye Irene; Alexander, Stanly W.; Gerungai, Natalia Y. T. (Manajemen Bisnis dan Keuangan Korporat, 2024)
The objective of accurate costing is to calculate and measure the cost of resources used with the greatest possible precision. In normal circumstances, the selling price of goods or services must cover the costs incurred by the company. This study will determine the application of the full costing method and the variable costing method in calculating the cost of production to determine the selling price at CV Emilysia Indo Bahari. The analysis is qualitative. The study results clearly show that the full costing method results in higher costs and selling prices compared to the variable costing method. The full costing method produces a selling price of IDR 30,824 for Baby Tuna size 6-10, while the company's selling price is IDR 20,500. The variable cost method produces a selling price of IDR 21,625, which is almost equal to the company's selling price.